Croisade Humanitaire . Humanity's Crusade
A Red Cross (CICR Geneva) propaganda film about Hungarian refugees fleeing the country after the crushing of the 1956 revolution. The film presents the daily activities of Hungarian refugees in a refugee center in Switzerland followed by their much awaited relocation to the United States.